MODIFIKASI PERMAINAN SCRABBLE UNTUK MENAMBAH PERBENDAHARAN PERMAINAN BAGI SISWA TUNANETRA DI SLB A YPLB MAJALENGKA - Herlangga, Heru (2015)
Penelitianinimerupakanpenelitiankualitatif dengan metode deskriptif.Penelitianinidilaksanakan pada bulan Mei 2015padaKelas VIIA SMPLB DI SLBA YPLB Majalengka.Fokusdaripenelitianiniadalahmodifikasipermainan scrabble untukmenambahperbendaharaanpermainanbagisiswatunanetraKelas VIIA SMPLB, DI SLBA YPLB Majalengka. Tujuandaripenelitianiniadalahuntukmenjelaskancaramodifikasipermainan scrabble, menjelaskanpengetahuansiswatentangbentuk dan fungsidarimasing-masingbagianalatpermainan scrabble, menggambarkanpemahamansiswatentangcaradanaturan main scrabble, menggambarkankemampuansiswatunanetradalammemainkanpermainan scrabble, menjelaskanpenilaiansiswatentangpermainan scrabblebagisiswatunanetra. Penelitian ini dilakukan dengan tujuan utama untuk memberikan gambaran atau deskripsi tentang kelayakan permaian scrabble bagi siswa tunanetra yang terefleksi dalam kemampuan siswa tunanetra memainkannya, sehingga permainan ini layak menjadi perbendaharaan permaianan bagi siswa tunantra. Hasil temuan penelitian menunjukkan bahwa modifikasi permainan scrabble layak menjadi perbendaharaan permainan bagi siswa tunanetra. Kelayakan permainan ini diidentifikasi dari hasil temuan yang menunjukkan bahwa siswa-siswa tunantera mampu memainkan permainan ini dengan baik tanpa hambatan yang berarti. Kemampuan mereka memainkan permainan scrabble dibuktikan dengan hasil temuan yang menunjukkan pencapaian siswa tunanetra dalam berbagai aspek terkait permainan scrabble yang mencakup pengetahuan mereka akan bentuk, bagian-bagian, dan fungsi dari masing-masing bagian alat scrabble, pemahaman yang baik tentang cara dan aturan main scrabble. Kelayakan permainan ini juga ditunjukkan dengan beberapa penilaian siswa tunanetra terhadap permainan ini.   This study is a qualitative study using a descriptive approach. This study was conducted in the period May 2015 to the Class VIIA SMPLB, SLBA YPLB Majalengka. The focus of the study was modification of scrabble game as contribution to game play collection for blind students at class VIIA SMPLB, SLBA YPLB Majalengka.The purpose of this study, among others, is to explain how to modify scrabble game, to explain the students' knowledge about the shape, parts and functions of each part in scrabble, to describe students' understanding of the ways and rules in scrabble game, to illustrate the ability of blind students in playing scrabble game, to explain the students' assessment on scrabble game, and to explain eligibility of scrabble game for blind students. This study was conducted to provide a reference for all parties concerned and gave special attention to the game for blind students, and they are expected to actualize the proliferation of efforts to facilitate the needs of blind students towards the playing activities. The design used in this study is using a naturalistic approach; therefore, this research emphasis on investigative efforts to study natural phenomena taking place in the overall complexity. The method used in this research is descriptive method. This research was conducted with the primary objective to provide a picture or description of the feasibility of game scrabble for blind students which was reflected in the ability of blind students to play it, so the game is worthy of being a treasury of games or for the blind students. Research findings indicate that the modification of scrabble game worthy of being a treasury of games for blind students. Feasibility of this game was identified from the findings that show that the blind students able to play this game well without major obstacles. Their ability to play a game of scrabble was stranghtened by the findings that show the blind students' achievement in various aspects related to the game of scrabble which covers their knowledge of shapes, parts, and functions of each part scrabble tool, a good understanding of the ways and rules of scrabble, and their ability to adapt to the game of scrabble. The feasibility of this game was also was supported by some positive assessment from the blind students. In addition scrabble game was proved to be very easily modified so that it can quickly be presented with a relatively low cost.